Few with ST-segment elevation myocardial infarction are diagnosed within 10 minutes from first medical contact, and women have longer delay times than men. (February 2020) - Muhrbeck, Josephine; Maliniak, Eli; Eurenius, Lars; Hofman-Bang, Claes; Persson, Jonas
Abstract: Background: Previous reports have questioned the feasibility and gender equality of obtaining a prehospital ECG within 10 minutes of ambulance arrival for patients with ST-segment elevation myocardial infarction (STEMI). The main objective of this study was to investigate the proportion of STEMI patients with a prehospital ECG within 10 minutes of ambulance arrival. The secondary objective was to study the gender differences in delay times in prehospital STEMI care. Methods: This study was a retrospective study based on 539 patients with STEMI at the investigating hospital. Ambulance and medical charts, as well as the national quality registry "SWEDEHEART", were reviewed for each patient for demographics and time information. Results: A prehospital ECG was obtained within 10 minutes of ambulance arrival for 99 (29%) of the men and 19 (14%) of the women, p = 0.001. Women had a 2 minutes longer delay between ambulance arrival and prehospital ECG (95% CI 0–4 min, p = 0.018) than men. Women also had a significantly longer patient delay. None of the other time intervals differed among men and women. Conclusions: Only for a minority of patients is a prehospital ECG taken within the recommended ten minutes from ambulance arrival. Women have longer patient delay times, as well as delay times to the acquisition of a prehospital ECG than men. Improvements of prehospital ECG acquisition and adjustments of the guidelines are warranted.